Anomali Hierarki Peraturan Perundang-Undangan dalam Kebijakan Pemangkasan Transfer ke Daerah - Aini Rahmania; Muhamad Khoerul Umam (Universitas Cokroaminoto Yogyakarta, 2027)
This study examines the anomaly in the hierarchy of laws and regulations concerning the policy of reducing Regional Transfers (TKD. The research employs a normative legal method using statutory and conceptual approaches. The findings reveal that a Presidential Instruction functions as an administrative policy instrument, while a Ministerial Regulation derives its legal legitimacy only when issued pursuant to a delegation of authority from higher-level legislation. The use of these two instruments as the legal basis for reducing TKD has the potential to create normative disharmony, legal uncertainty, and undermine the principles of legality and regional autonomy. From the perspective of the Stufenbau des Recht theory, this practice is inconsistent with the hierarchical structure of legal norms in a state governed by the rule of law. Therefore, the formulation of national fiscal policies should adhere to the established hierarchy of laws and regulations to ensure legal certainty and maintain the consistency of the national legal system.